Finite element analysis of filler shape in photopolymerization additive manufacturing using the Fusion RSA-RVE algorithm - Omar, Syah Mohd Amin; Hamat, Sanusi; Hussin, Mohd Sabri; Wan Draman, Wan Nur Atiqah; Kelly, Piaras; Ahamad Suffin, Muhamad Qauyum Zawawi; Ariffin, Mohd Azam (National University of Malaysia, 2025)
Photopolymerization-based additive manufacturing has become a key technology due to its advantages, such as low energy consumption and rapid processing. However, optimizing the mechanical properties of composite materials produced through this process remains a challenge. The impact of filler geometry on the mechanical performance of photopolymerized composites has not been fully explored. Shrinkage stresses during polymerization, especially in acrylate-based materials, can lead to brittleness and cracking, limiting their structural integrity and industrial application. This study aims to investigate the influence of different filler shapes and densities on the tensile strength, strain, and stress distribution of composite materials fabricated through photopolymerization. A Finite Element Representative Volume Element (FE-RVE) approach was employed, integrating ABAQUS scripting with Random Sequential Adsorption (RSA) for filler modelling. Non-linear dynamic tensile simulations were conducted to analyse the mechanical behaviour of composites with three filler shapes: sphere, prism, and polyhedron. Experimental validation was performed using ASTM D-638 tensile tests to ensure the accuracy of the simulations. The study anticipates that filler geometry significantly influences the mechanical performance of composites. Polyhedron-shaped fillers are expected to exhibit the highest tensile stress due to their superior stress distribution capabilities, while prism fillers may demonstrate enhanced flexibility. These findings aim to provide valuable insights into designing optimized composites for industrial applications, such as automotive and high-performance engineering.